Simultaneous Determination of Caffeine and Pyridoxine in Energy Drinks using Differential Pulse Voltammetry at Glassy Carbon Electrode Modified with Nafion®. Issue 8 (22nd May 2019) - Farag, Amir Shaaban; Pravcová, Kateřina; Česlová, Lenka; Vytřas, Karel; Sýs, Milan
Abstract: A new voltammetric method for simultaneous determination of caffeine and pyridoxine present in different types of commercial energy drinks has been developed. This electroanalytical method is based on anodic oxidation of these biologically active nitrogen‐containing heterocycles at glassy carbon electrode covered with thin layer of sulfonated fluoropolymer Nafion® using differential pulse voltammetry in 0.1 M Britton‐Robinson buffer of pH 4.5 at potential step 5 mV, potential amplitude 70 mV, and scan rate 50 mV/s. Linear ranges for caffeine and pyridoxine determination were 63.1–600 μM and 7.5–200 μM with the detection limits of 18.9 and 2.2 μM, respectively. It was validated using high‐performance liquid chromatography with spectrophotometric detection. Obtained results have shown that voltammetric approach is very simple and low‐cost analytical method which can be used for routine determination of caffeine and pyridoxine in energy drinks. Abstract :